2021
DOI: 10.1016/j.jid.2021.02.764
|View full text |Cite
|
Sign up to set email alerts
|

New Frontiers in Psoriatic Disease Research, Part I: Genetics, Environmental Triggers, Immunology, Pathophysiology, and Precision Medicine

Abstract: Psoriasis is a chronic inflammatory condition characterized by systemic immune dysregulation. Over the past several years, advances in genetics, microbiology, immunology, and mouse models have revealed the complex interplay between the heritable and microenvironmental factors that drive the development of psoriatic inflammation. In the first of this two-part review series, the authors will discuss the newest insights into the pathogenesis of psoriatic disease and highlight how the evolution of these scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 204 publications
(151 reference statements)
0
22
0
1
Order By: Relevance
“…3,4 Furthermore, the inflammation results in keratinocyte hyperproliferation, dysfunction and production of cytokines, thus sustaining the inflammatory loop. 4,5 Several treatment options exist for psoriasis; however, traditional systemic drugs have well-known clinical limitations and potential side effects. 6 Ultraviolet (UV) irradiation with either artificial UVA or UVB light or with natural sunlight is another treatment option.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Furthermore, the inflammation results in keratinocyte hyperproliferation, dysfunction and production of cytokines, thus sustaining the inflammatory loop. 4,5 Several treatment options exist for psoriasis; however, traditional systemic drugs have well-known clinical limitations and potential side effects. 6 Ultraviolet (UV) irradiation with either artificial UVA or UVB light or with natural sunlight is another treatment option.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of psoriasis is not fully elucidated. However, T cells and associated cytokines, such as interleukin (IL)‐17 and IL‐23, play a major role by recruiting a plethora of immune cells such as dendritic cells (DCs), Langerhans cells (LCs), neutrophils and macrophages to the skin 3,4 . Furthermore, the inflammation results in keratinocyte hyperproliferation, dysfunction and production of cytokines, thus sustaining the inflammatory loop 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, innovative biologic therapies targeting pathogenic cytokines have improved the clinical outcomes of inflammatory dermatoses, such as psoriasis and atopic dermatitis (Liu et al, 2020;Salvati et al, 2021). Relevant studies in experimental murine models have further revealed the pathological significance of networks involving proinflammatory cytokines, including interleukin (IL)-17, IL-22, IL-23, and tumor necrosis factor (TNF)  which mediate aberrant keratinocyte and inflammatory cell interactions in inflammatory cutaneous lesions (Bieber, 2020;Chiricozzi et al, 2018;Yan et al, 2021). Given the limited effectiveness of biologic therapies for chronic inflammatory dermatoses, a further understanding of the mechanisms of inflammatory circuits contributing to cutaneous lesions is required.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors, which play important roles in both the predisposition and the aggravation of psoriasis, have been revealed and appreciated. Environmental triggers of psoriasis include stress, surgery, alcohol abuse, smoking, and, most prominently, infection [3,4]. The clinical correlation between guttate psoriasis (GP) and streptococcal pharyngitis is well established, indicating a bridge between psoriasis and bacterial infection [5].…”
Section: Introductionmentioning
confidence: 99%